PROTOTYPE KARTU PINTAR KAMAR TIDUR MENGGUNAKAN SENSOR INFRARED DAN PHOTODIODA BERBASIS ARDUINO UNO - Ikhsan Parinduri ((JurTI) Jurnal Teknologi Informasi, 2017)
Abstract - Smart cards, physically, are plastic cards the size of a credit card that can be filled with data for various purposes. A number of smart card uses include electronic cash payments, attendance systems, train and bus ticket subscription cards, toll road payments, and others. Smart Card Design for bedrooms using photodiode sensors and Arduino Uno based infrared sensors have succeeded well according to the procedure. The work system of the bedroom smart card series is very useful for efficient use of electricity in the household. The working system of photodiode sensors and infrared sensors is very both in a series that functions as a light sensor Keywords - Smart Card, Arduino Uno